The influence of closed or open grip type during a pull-up test to exhaustion - Bartolo Luca Di; Ficarra Salvatore; Polizzi Davide; Drid Patrik; Paoli Antonio; Palma Antonio; Thomas Ewan; Bianco Antonino (Sciendo, 2023)
Study aim: The aim of this study is to assess whether a closed (CG) or open grip (OC) can influence the maximum number of repetitions during the pull-up test to exhaustion.